2021
DOI: 10.1126/sciadv.abk2904
|View full text |Cite
|
Sign up to set email alerts
|

Big or small, patchy all: Resolution of marine plankton patch structure at micro- to submesoscales for 36 taxa

Abstract: Underwater imaging resolves plankton patch structure for 36 taxa in continental and oceanic waters of a western boundary current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 76 publications
2
25
1
Order By: Relevance
“…The majority of the patches distinguished in this study were longer than 10 km (Supplementary Table 2), which agrees with the ranges presented in the most recent study of the wide spectrum of plankton patchiness (Robinson et al, 2021). However, those authors concluded that longer sampling transects (50 to 100 km) are needed to elucidate the true patch length for copepods and phytoplankton groups.…”
Section: The Factors That Could Play An Important Role In Structuring...supporting
confidence: 91%
See 2 more Smart Citations
“…The majority of the patches distinguished in this study were longer than 10 km (Supplementary Table 2), which agrees with the ranges presented in the most recent study of the wide spectrum of plankton patchiness (Robinson et al, 2021). However, those authors concluded that longer sampling transects (50 to 100 km) are needed to elucidate the true patch length for copepods and phytoplankton groups.…”
Section: The Factors That Could Play An Important Role In Structuring...supporting
confidence: 91%
“…The results of this study showed that only 6 out of the 94 studied patches exceeded horizontally 50 km, 9 exceeded 40 km, and 21 patches were longer than 20 km (Supplementary Table 2). Despite the fact that this study was restricted to the upper 50-meters, the vertical extension of most of the detected patches (26 m) exceeds considerably the limit (several meters) for thin plankton layers (Dekshenieks et al, 2001;McManus et al, 2005;Benoit-Bird et al, 2013) and greatly ranks to the ranges (10-30 m) recently observed for the 36 plankton taxa (Robinson et al, 2021).…”
Section: The Factors That Could Play An Important Role In Structuring...contrasting
confidence: 53%
See 1 more Smart Citation
“…The variability between the 2 plankton collection gears observed herein (~35%) can therefore be considered as relatively low, and thus validates the sampling efficiency of the Coryphaena. Such discrepancies between sampling gears have been shown in many past studies (e.g., Herdman, 1921;Barnes and Marshall, 1951;Anraku, 1956 andWiebe, 1968), and are typically due to net avoidance, mesh extrusion, escapement, and especially to non-random distribution of plankton (local plankton patchiness; Robinson et al, 2021). Indeed, unlike laboratory experiments where all variables are isolated and controlled, field trials to validate technologies such as the Coryphaena and DN, induce variability dependent on local conditions.…”
Section: Coryphaenamentioning
confidence: 95%
“…Indeed, unlike laboratory experiments where all variables are isolated and controlled, field trials to validate technologies such as the Coryphaena and DN, induce variability dependent on local conditions. Part of the variability observed between instruments could therefore result from plankton heterogeneity in the ocean (Robinson et al, 2021). Notably, although performed in the same area, the Coryphaena sampling took on average 25 min (maximum 55 min), while the DN needed between 1-2 hours to filter ca.…”
Section: Coryphaenamentioning
confidence: 99%